Internalisation of Disability as a Social Phenomenon in the Reality of Inclusive Education - Galkienė, Alvyra (Pedagogika, 2016)
Otherness of students that alters their aesthetical appearance, reduces physical abilities or limits cognitive potential may determine the difference in levels of individuals and different nature of interpersonal relationships. The research aimed at finding the answer to the question: What attitudes of educators and inclusively educated students result in internalized conception of disability as a social phenomenon?